Variability of PDYN and OPRK1 genes in four Argentinian populations and its genetic association with clinical variables related to acute postsurgical pain - Di Santo Meztler, Gabriela Paula (2022)
Several population studies showed an association between variation in pain sensitivity and genetic polymorphisms located in Prodynorphin (PDYN) and Kappa Opioid Receptor (OPRK1) human genes. We analysed polymorphisms of these two genes to characterise their variation in Argentinian populations, as well as to evaluate their association with acute pain sensitivity. We studied 11 genetic markers in individuals from four locations in Argentina (Ciudad Autónoma de Buenos Aires, La Plata, Resistencia, and Misión Nueva Pompeya), calculated the population parameters, and evaluated the possible association among pain sensitivity, clinical, and genetic variables through a Generalised Estimating Equation model. High linkage disequilibrium was observed in the four populations for both genes, and significant differences were found among frequencies of Argentinian populations and those from other continents reported in the 1000 Genomes Project. Four PDYN gene polymorphisms from 3´ untranslated region and exon 4 showed association with acute pain sensitivity. One genotype of each of these polymorphisms was associated with a higher pain sensitivity, probably related with the activation of the N-methyl-D-aspartate (NMDA) receptors. We found a strong association with acute pain for the following clinical variables: 1) time after surgery, 2) intravenous klosidol supplied every 8 h, and 3) type of incision. Our results highlight the importance of a regional study of genetic variants which influence pain sensitivity and analgesic response.